THE LATE TRIASSIC-HETTANGIAN BIVALVES TURNOVER IN LOMBARDY (SOUTHERN ALPS) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1991)
One of the major mass extinctions of the Phanerozoic took place at the Rhaetian-Hettangian boundary. According to some researchers, it might have been preceded by a minor event at the end of the Carnian. The faunal association present in the Late Trixsic formations of Lombardy and their changes related with the lithofacies changes are analysed here. In the Carnian Gorno Formation and Val Sabbia Sandstone, five bivalve assemblages have been distinguished. From the trophic analysis of these molluscs, we observe the infaunal suspension feeders predominance in the 1st and 2nd assemblage. They are gradually replaced by epibyssate species in the following associations, closely related with the lithofacies changes. In the overlying Norian Dolomia Principale, most bivalves disappear. They are replaced by species of Neomegaladon, Isognomon and gastropods. It is pointed out that this decline is not due to mass extinction, but to the settlement of different conditions in the basin which fitted better the euryhaline bivalve assemblages. In the overlying Riva di Solto Argillite, Zu Limestone and Conchodon Dolomite, 4 bivalve assemblage zones have been distinguished. Both, the new genera appearance and the number of species increase are closely linked to the substitution of calcareous facies of peritidal platform with argillaceous and arenaceous sequences of inner basin. In the Hettangian Sedrina Limestone, the fauna treated by Gaetani (1970), rich in bivalves, is examined. The diversity and the phyletic relationship of this species with those of the Rhaetian zones are pointed out. The diversity, the origination and extinction rate are calculated for the bivalve species of Lombardy and for the Megalodontidae and Dicerocardiidae revised by Végh-Neubrandt (1982). Eventually, some morphologic changes in the phyletic lineage of megalodontids have been pointed out too. Concluding, faunal crisis like mass extinction is not recorded by the bivalve assemblages of the Late Triassic of Lombardy and Southern Alps in general. They reflect pseudoextinctions, sudden and severe turnover, certainly depending on the changing environmental conditions. The affinity among the late Rhaetic bivalves and those of the Hettangian demostates that the big faunal crisis at the Rhaetian-Hettangian boundary in Lombardy is traceable back to a rapid faunal turnover consequent to the rifting and sinking of the carbonate platform.
Keywords: Bivalves turnover; Late Triassic-Hettangian; Lombardy (Italy).